STRATEGI KOMUNIKASI PEMASARAN AEON MALL BSD CITY DALAM MENINGKATKAN JUMLAH PENGUNJUNG DI MASA PANDEMI COVID-19 - Hala Amira Sadiah, (2021)
The COVID-19 pandemic has caused shopping centers to suffer losses estimated at 6 trillion. One of the shopping centers that suffered losses was AEON Mall BSD City, a mall from Japan which also experienced a decrease in traffic (number of visitors). So AEON Mall BSD City is trying to increase traffic through a marketing communication strategy. This study aims to determine the marketing communication strategy carried out by AEON Mall BSD City in increasing the number of visitors during the COVID-19 pandemic. This study uses a qualitative approach with descriptive research and case study methods. This research was analyzed by using the STOP-SIT analysis model. The marketing communication strategy carried out by AEON Mall BSD City to increase the number of visitors through 6 marketing communication tools, namely: advertising, public relations, sales promotion, direct marketing, sponsorship, and personal selling